Welcome culture in German schools: teachers’ perspectives - Klöpfer, Lea; Lebeda, Maria; Waburg, Wiebke (Frontiers in Education, 2024)
The secondary analysis focuses on teachers’ perspectives on welcome culture (Willkommenskultur) in German schools for pupils who have fled from Ukraine. The following research question was pursued: What aspects of the welcome culture become apparent in statements of teachers? Data from five group discussions with individuals from primary and secondary schools and an educational institution in Rhineland-Palatinate were analyzed. Participants included teachers (n=12), school principals (n=2), and one director. The study indicates that refugees from Ukraine are treated differently from refugees originating from Syria or other countries; these differences can be recognized at both the individual and societal levels.